PENGARUH PENAMBAHAN SERBUK LIMBAH MARMER TERHADAP KUAT TEKAN MORTAR - Permadi, Danu (Journal of Civil Engineering and Infrastructure Technology, 2025)
One type of mortar used in the process of making walls and plastering is lime mortar. In this study, marble waste will be utilized to increase quality. The use of waste marble as a substitute for a portion of the weight of cement can produce a plastic mortar, making it easy to work with and the mortar is more watertight. Because marble waste has a fairly high calcium content, it is hoped that it will be able to become a binder and can reduce cement during the mortar making process. This study discusses the effect of mortar with marble waste substitution of 0%, 20%, 25% and 30% by weight of cement. Compressive strength testing was carried out at the age of 3, 7, 14, 21 and 28 days. From the test results it can be seen that for all variations of mortar there has been an increase in both the bulk density of the mortar and the compressive strength of the mortar at each age, but has no effect on the addition of the value of the unit weight or compressive strength on the normal mortar, with the optimum value found in the addition of marble waste powder of 25% results in a compressive strength of 15.33 MPa with a bulk density of 2.04 gram/cm3. Judging from the compressive strength obtained based on SNI 03-6882-2002 concerning mortar specifications, for all variations of mortar including type S lime mortar.